ROLE OF DIET AND LIFESTYLE IN THE PREVENTION OF MADHUMEHA (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda is a natural health care system that originated in India since the beginning of civilization. It is described by Acharaya Charak that to achieve Purushartha Chatushtaya, Arogya is necessary. Ayurveda strongly emphasize on preventive and promotive aspects of health rather than curative. The concepts of Dincharya, Ritucharya, Sadvritta, and Achara Rasayana along with guidelines for healthy diet and lifestyle is well established in Ayurveda, but in current scenario, hardly anyone aptly follow it. As a result, there is tremendous rise in lifestyle disorders as pandemics, Diabetes being most menacing among them. Diabetes is the fourth leading cause of global death by disease. Type 2 DM is responsible for approximately 90% of cases. In Ayurveda, Madhumeha one of the types of Vataja Prameha is compared to Diabetes Mellitus because of having similarities of disease in respect to etiopathogenesis, clinical features and prognosis. The main causes of Madhumeha are lack of exercise, improper food habits, excessive intake of food having Snigdha and Guru Guna and food which causes vitiation of Kapha Dosha. Modern therapeutics has many limitations but Ayurvedic principles of management can help the patient to control blood glucose level and have better routine life. So Ayurvedic lifestyle guidelines of adopting a healthy dietary pattern together with physical activity are valuable tools in the prevention of Madhumeha.